Do antisocial and prosocial traits vary across different socioeconomic status groups in a sample of South African adolescents? - Knipe, Candice (Department of Psychology, 2025)
South Africa, globally recognized for its high crime rates, prompts a nuanced exploration of the interconnections between crime, antisocial traits, and protective factors such as prosocial traits within its unique context. The current research therefore aimed to examine the prevalence of antisocial and prosocial traits in adolescents from different socioeconomic backgrounds within this context. Existing research predominantly focuses on higher income countries, leaving a notable gap in understanding within the South African low - to middle income country landscape. Despite its middle-income classification, South Africa grapples with pervasive inequality with much of the population living in poorer socioeconomic settings, emphasizing the importance of investigating the extent of both antisocial and prosocial traits across diverse socio-economic settings. The study utilized a cross-sectional and correlation design. Online self-report questionnaires were used to gather demographic and socio-economic status information, antisocial scores using the Inventory of Callous Unemotional Traits, and prosocial scores using the Prosocial Tendency Measure. The sample, comprised of South African adolescents, of which 52% were male, 45% were female, 3% were non-binary, aged 13-18 (N=44). I used multiple linear regression to analyse the collected data. The study's findings demonstrated that gender emerged as a significant predictor for both prosocial and antisocial behaviours among adolescents (ICU: p=0.03; PTM: p=0.04). However, the results did not support a significant association between socioeconomic status and these outcomes. This research contributes to a more comprehensive understanding of the factors shaping antisocial and prosocial traits, particularly during adolescence, within the South African context